Preparation of Radioactive Gold Nanoparticle by Neutron Activation - Awaludin, Rohadi (UI Scholars Hub, 2009)
Preparation of Radioactive Gold Nanoparticle by Neutron Activation. It was reported that gold nanoparticle could be used for cancer therapy using thermal effect. It is possible to kill cancer cells using radiation of radioisotope. Study on preparation of radioactive gold by neutron activation at central irradiation position (CIP) of G.A. Siwabessy reactor with neutron flux 1.26 x 1014 neutron s-1cm-2 has been carried out. It was revealed that a radioisotop of gold (198Au) was produced by neutron activation from natural gold. Calculation results showed that 198Au with radioactivity of 0.366 Bq, 2.93 Bq, 9.90 Bq and 23.4 Bq was produced for nanoparticle with diameter of 100, 200, 300 and 400 nm by neutron irradiation for 12 days. The saturation factor was 96.5%. After 10 days of decay, the radioactivity was 0.027 Bq, 0.223 Bq, 0.753 Bq and 1.78 Bq in nanoparticle with diameter of 100, 200, 300 and 400 nm. The radionuclide impurities were 108Ag, 110mAg, 64Cu, 66Cu, 205Pb and 209Pb with the total radioactivity was 4.31 x 10-5 % of the total radioactivity of 198Au at the end of irradiation.